ZnO-BiOCl Nanocomposite for Photocatalytic Degradation of Organic Dye - Li, Benxia; Wang, Yanfen; Wu, Yulei; Xu, Chuyang (Asian Journal of Chemistry, 2012)
ZnO-BiOCl nanocomposite was synthesized via a two-step process where the precursor was first prepared by a facile coprecipitation method and then was calcined at 500 ºC under air atmosphere. The nanocomposite is composed of porous ZnO nanoplates and BiOCl nanoparticles. For photodegradation of rhodamine B under the simulated sunlight irradiation, the ZnO-BiOCl nanocomposite exhibited higher photocatalytic efficiency than pure ZnO.